The natural progression and outcomes of adrenal incidentaloma: A systematic review and meta-analysis - Loh, Huai Heng; Yee, Anne; Loh, Huai S.; Norlela, Sukor; Nor Azmi Zmi, Kamaruddin (National Center for Biotechnology Information Search database, 2017)
Introduction: Long-term outcome of patients with adrenal incidentaloma (AI) is unknown. The aim of this study was to systematically summarize the follow-up and outcome of clinically silent AI who do not undergo surgery. Evidence Acquisition: All major databases and medical literature in English-language, published from 1998 to May 2015, were systematically searched for publications on AI. Primary endpoint was hormonal hyper function; secondary endpoints were time from diagnosis to study endpoint and the outcome of adrenalectomy. Meta-analysis was performed using both qualitative and quantitative approach. Evidence Synthesis: A total of 11 publications were included. Total sample size was 1298 patients. Mean followup duration was 44.2 months. There were 82 patients confirmed to have subclinical Cushing's syndrome at diagnosis, with 1.79% new cases at the end of follow up (95% CI, 0.002 to 0.045). Incidence of Cushing's syndrome was 0.7% (95% CI, 0.001 to 0.013) and pheochromocytoma 0.4% (95% CI, 0.001 to 0.008). The mean tumor size was 2.52cm, with mean increment of 0.03cm to 2.9cm at the end of follow up. About 3% of patients ended up with surgery (95% CI, 0.01 to 0.05) but none were due to primary adrenal malignancy. Time of greatest risk of developing Cushing's syndrome and pheochromocytoma was between months 36 and 42 (hazard rate 14%), and between months 48 and 54 (hazard rate 7%) respectively. Conclusions: Malignant change in non-functioning AI is rare. The risk of developing overt disease over the followup period is low. A less stringent imaging and functional work-up interval can be considered.